2011
DOI: 10.1103/physrevb.83.174513
|View full text |Cite
|
Sign up to set email alerts
|

Charge stripes in the two-orbital Hubbard model for iron pnictides

Abstract: The two-orbital Hubbard model for the pnictides is studied numerically using the real-space Hartree-Fock approximation on finite clusters. Upon electron doping, states with a nonuniform distribution of charge are stabilized. The observed patterns correspond to charge stripes oriented perpendicular to the direction of the spin stripes of the undoped magnetic ground state. While these charge striped states are robust when the undoped state has a Hubbard gap, their existence when the intermediate-coupling magneti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…The calculation for stripes in pnictides was carried out by members of our group and the results were reported in Ref. [88], and some results are reproduced in this section. In Fig.…”
Section: Are There Charge Stripes In Models For Pnictides?mentioning
confidence: 98%
“…The calculation for stripes in pnictides was carried out by members of our group and the results were reported in Ref. [88], and some results are reproduced in this section. In Fig.…”
Section: Are There Charge Stripes In Models For Pnictides?mentioning
confidence: 98%
“…[23][24][25][26] The two-orbital Hubbard model studied here is defined as: z i,α = (1/2)(n i,α,↑ − n i,α,↓ ). U , U , J, and J are the Kanamori parameters.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Mean-field approximations have already been applied to two-orbital Hubbard models at T =0, 25,26 showing several phases with increasing U/W : a paramagnetic metal, a metal with (π, 0) spin order, and an insulator also with (π, 0) spin order. These previous T =0 studies and others [1][2][3][4] showed that J/U ∼ 0.15−0.30 is relevant for FeSC, and we will fix J/U = 0.25 in all the results below.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Numerical methods generally also use various simplifications for modeling the Hamiltonian of the two-orbital model. Charge stripes states were obtained in [7] within the real-space Hartree-Fock approximation away from the half-filling. Quasi one-dimensional "ladder" geometry was used in [8] for the study of the properties of the ground state of the two-orbital model by density matrix renormalization group approach.…”
Section: Introductionmentioning
confidence: 99%